The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1186/s12864-018-4608-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel MITEs (miniature inverted-repeat transposable elements) in Coxiella burnetii: implications for protein and small RNA evolution

Abstract: BackgroundCoxiella burnetii is a Gram-negative gammaproteobacterium and zoonotic agent of Q fever. C. burnetii’s genome contains an abundance of pseudogenes and numerous selfish genetic elements. MITEs (miniature inverted-repeat transposable elements) are non-autonomous transposons that occur in all domains of life and are thought to be insertion sequences (ISs) that have lost their transposase function. Like most transposable elements (TEs), MITEs are thought to play an active role in evolution by altering ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

5
2

Authors

Journals

citations
Cited by 18 publications
(38 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…However, little is known about the roles for IHF and DksA in C. burnetii . The consensus IHF-binding site occurs in a C. burnetii selfish genetic element, suggesting that this binding sequence is maintained in the pathogen [31]. Similarly, a role for DksA in C. burnetii ’s stringent response has been suggested, although no correlations could be drawn [56].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, little is known about the roles for IHF and DksA in C. burnetii . The consensus IHF-binding site occurs in a C. burnetii selfish genetic element, suggesting that this binding sequence is maintained in the pathogen [31]. Similarly, a role for DksA in C. burnetii ’s stringent response has been suggested, although no correlations could be drawn [56].…”
Section: Discussionmentioning
confidence: 99%
“…RNA was folded using mFold [81] and visualized with the Visualization Applet for RNA [82]. Analyses of RNA-Seq data were carried out as previously described [31]. Briefly, raw fastq files were concatenated, quality-filtered with the FASTX toolkit (http://hannonlab.cshl.edu/fastx_toolkit/) and then clipped, aligned, and filtered with Nesoni version 0.128 tools (http://www.vicbioinformatics.com/software.nesoni.shtml).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Northern blots also showed that CbsR12 was upregulated in SCVs versus LCVs in ACCM-2 and revealed two distinct sizes of the sRNA, suggesting that either an alternative transcription start site (TSS) or RNase processing of the sRNA was responsible. In a subsequent study, CbsR3 and CbsR13 were found to originate from transcribed loci of a selfish genetic element, termed QMITE1 (38). However, despite the identification and verification of several CbsRs, none has been functionally characterized to date.…”
mentioning
confidence: 98%
“…RNA was folded using Mfold (73) and visualized with Visualization Applet for RNA (74). Analyses of RNA-Seq data were carried out as previously described (38). Briefly, raw fastq files were concatenated, quality filtered with the FASTX toolkit (http://hannonlab.cshl.edu/fastx_toolkit/), and then clipped, aligned, and filtered with Nesoni version 0.128 tools (http://www.vicbioinformatics.com/software.nesoni.shtml).…”
mentioning
confidence: 99%